Epidemiology and treatment outcome of nasopharyngeal carcinoma in a low-incidence population – a DAHANCA analysis in Denmark 2000–2018 - Erik Schiess; Kristian H. Jensen; Morten H. Kristensen; Jørgen Johansen; Jesper G. Eriksen; Christian Maare; Maria Andersen; Mohammad Farhadi; Christian R. Hansen; Jens Overgaard; Lisa L. Hjalgrim; Giedrius Lelkaitis; et al. (Acta Oncologica)
Introduction: Nasopharyngeal carcinoma (NPC) is a rare disease and most studies have therefore been conducted in endemic areas. The aim of this study was to describe epidemiology and treatment outcomes of NPC in a population-based, non-endemic setting.